The land of murder, cannibalism, and all kinds of atrocious crimes? Maori and crime in New Zealand 1853-1919 - Bull, Simone (The British journal of criminology, 2004)
A novel longitudinal profile of Maori crime' from 1853 to 1919 is presented. It constitutes an additional step towards understanding how the indigenous Maori have come to be over-represented in New Zealand's post-colonial criminal justice system. The profile is explained in terms of culture conflict, literal normlessness and pursuit of the illusion of state control. The British colonial government also criminalized Maori whenever they rebelled'. In the statistics presented here, gross violations of human rights and the criminalization of Maori independence are reflected in four distinct episodes: around the mid-1860s, 1881, 1897 and 1911. The analysis points to conflict and critical criminology as the principal paradigms through which the crimes' of the powerful colonial state converted Maori into criminals